An approach to the effects of longevity, sexual maturity, and reproduction on telomere length and oxidative stress in different Psittacidae species - Domínguez-de-Barros, Angélica; Sifaoui, Inés; Borecka, Zuzanna; Dorta-Guerra, Roberto; Lorenzo-Morales, Jacob; Castro-Fuentes, Rafael; Córdoba-Lanús, Elizabeth (Frontiers in Genetics, 2023)
Aging is a multifactorial process that includes molecular changes such as telomere shortening. Telomeres shorten progressively with age in vertebrates, and their shortening rate has a significant role in determining the lifespan of a species; however, DNA loss can be enhanced by oxidative stress. The need for novel animal models has recently emerged as a tool to gather more information about the human aging process. Birds live longer than other mammals of the same size, and psittacine species are the most persevering of them, due to special key traits. We aimed to determine telomere length by qPCR, and oxidative stress status using colorimetric and fluorescence methods in different species of the order Psittaciformes with different lifespans. We found that telomeres shorten with age for both long- and short-lived birds (p<0.001 and p=0.004, respectively), with long-lived birds presenting longer telomeres than short-lived ones (p=0.001). In addition, short-lived birds accumulated more oxidative stress products than long-lived birds (p=0.013), who showed a better antioxidant capacity (p<0.001). Breeding was found related to telomere shortening in all species (p<0.001 and p=0.003 for long- and short-lived birds). Short-lived birds, especially breeding females, increased their oxidative stress products when breeding (p=0.021), whereas long-lived birds showed greater resistance and even increased their antioxidant capacity (p=0.002). In conclusion, the relationship between age and telomere length in Psittacidae was verified. The influence of breeding increased cumulative oxidative damage in short-lived species, while long-lived species may counteract this damage.